Elimination of Gear Clearance for the Rotary Table of Ultra Heavy Duty Vertical Milling Lathe Based on Dual Servo Motor Driving System - Hui Jiang; Hongya Fu; Zhenyu Han; Hongyu Jin (Applied Sciences, 2020)
The effective way to improve the position accuracy of rotary table of ultra-heavy vertical milling lathe is to reduce or even eliminate the clearance of mechanical transmission structure. In this paper, a useful method for eliminating the gear clearance of C axis of heavy duty machine tool is proposed based on dual servo motor driving system. The principle of double gear anti-backlash is explained and the process of clearance elimination is determined by adjusting the driving torques of the two motors. The dynamic model of the driving system of the dual servo motor is established, so as to find the non-linearity of the clearance, wear and tooth clearance in the drive system. According to the dynamic model and simulation results, the master-slave control parameters of the dual servo motor system are optimized in order to eliminate the clearance and improve the accuracy of the dual drive C-axis. Experiments are carried out to verify the validity of the proposed anti-backlash method. The experimental result also shows that the indexing accuracy of the table has been improved by more than 50% under different working conditions.